Zur Frage pleistozäner Vergletscherung im Harz und Thüringer Wald - Reichelt, Günther (ERDKUNDE, 1964)
There are no features in the uppermost parts of the Harz Mountains and Thuringian Forest which could be identified as of undoubted glacial origin. On the other hand there are fairly frequent occurrences of moraine-type gravel which occur in certain horizons and pockets of the exten sive periglacial gravel sheets. Faceted boulders and the discovery of striated boulders within the scree of the Rauhügel (Phycode schists) support these observations so that a firn cover on the high plateaux of both mountains down to about 800 m. above sea level must be assumed. The climat ic snow line probably lay somewhat higher. Indications of genuine glaciation occur - if at all - in the Beerberg area of the Thuringian Forest where short valley glaciers reach ing down to a little below 800 m. above sea level may perhaps be reckoned with. Stratigraphical data show that the firn cover existed in the second advance phase of the Würm glaciation and on the Beerberg lasted possibly until the Würm maxi mum. The other phases of the late Pleistocene are represented only by periglacial debris.